The use of active mixed-mode S-parameters to analyze differentially fed phased arrays - Yupeng Zheng; Shaoqiu Xiao (AIP Advances)
This paper proposes an improved theory of active mixed-mode S-parameters for analyzing and designing differentially fed phased arrays (DF-PAs). The active mixed-mode S-parameters characterize the reflection and conversion of differential and common modes in N-pair networks under arbitrary excitation. These S-parameters are derived as the weighted average of the active single-ended S-parameters of the two ports. To validate the theory, differentially fed circular microstrip phased arrays are implemented. Experimental results demonstrate that active differential reflection and conversion coefficients effectively characterize the scattering performance of DF-PAs.